A species-discriminatory single-nucleotide polymorphism set reveals maintenance of species integrity in hybridizing European white oaks (Quercus spp.) despite high levels of admixture. (8th January 2020) - Reutimann, Oliver; Gugerli, Felix; Rellstab, Christian
Abstract: Background and Aims: Hybridization and introgression play an important role in the evolution and diversification of plants. To assess the degree of past and current hybridization, the level of genetic admixture in populations needs to be investigated. Ongoing hybridization and blurred species separation have made it challenging to assign European white oak taxa based on leaf morphology and/or genetic markers and to assess the level of admixture. Therefore, there is a need for powerful markers that differentiate between taxa. Here, we established a condensed set of single-nucleotide polymorphism (SNP) markers to reliably differentiate between the three most common oak species in temperate European forests ( Quercus robur, Q. petraea, Q. pubescens ) and to assess the degree of admixture in a large set of selected Swiss populations. Methods: A training set of 194 presumably pure reference samples from Switzerland and Europe was used to assign 633 test individuals with two different approaches (population genetic-based/Bayesian vs. assumption-free/discriminative classifier) using 58 selected SNPs from coding regions. Admixture was calculated at the individual and population level with the Shannon diversity index based on individual assignment probabilities. Key Results: Depending on the approach, 97.5–100 % of training individuals were assigned correctly, and additional analyses showed that the established SNP set could be further reduced while maintaining its discriminatory power. The two assignment approaches showed high overlap (99 %) in assigning training individuals and slightly less overlap in test individuals (84 %). Levels of admixture varied widely among populations. Mixed stands of Q. petraea and Q. pubescens revealed much higher degrees of admixture than mixed stands of the other two taxon pairs, accentuating high levels of gene flow between these two taxa in Switzerland. Conclusions: Our set of SNPs warrants reliable taxon discrimination with great potential for further applications. We show that the three European white oak taxa have largely retained their species integrity in Switzerland despite high levels of admixture.